ASPECTOS CUANTITATIVOS DE LA FAUNA PARASITARIA DE LAS CACHARAS PSEUDOPLATYSTOMA FASCIATUM Y P. TIGRINUM (SILURIFORMES: PIMELODIDAE) DEL RÍO JAMARI, ARIQUEMES, RONDÔNIA, BRASIL - Lago Carvalho, Angélica (2019)
Pseudoplatystoma (Bleeker, 1862) species are of commercial importance in the region of Rondônia, however studies with the species are scarce, so the objective of the research was to carry out a diagnosis of the composition and structure of the parasite communities of Pseudoplatystoma fasciatum (Linnaeus, 1766) and P. tigrinum (Valenciennes, 1840) of the river basin Jamari, Ariquemes - RO, Brazil. During the period from November / 2016 to February / 2018, 50 specimens of P. tigrinum and 51 specimens of P. fasciatum were collected. Of the total sampled fish, 45 specimens of P. tigrinum and 51 specimens P. fasciatum were parasitized by at least one species of parasite presenting a prevalence level of 90% and 100%, respectively. In the parasitic infrapopulations of P. tigrinum, the groups with the highest prevalence rates were nematodes, with larvae being the largest representative of the group, followed by monogenean Vancleaveus ciccinus Kritsky, Thatcher e Boeger, 1986 and for P. fasciatum the parasite helminths that presented the highest prevalence level were the Cestoda groups: Megathylacus sp. Woodland, 1934; Harriscolex sp. Rego, 1987; Monticellia sp. La Rue, 1911; Nominoscolex sp. Woodland, 1934; Nematoda: larvae; Eustrongylides sp. Jägerskiöld, 1909; Cucullanus sp. Müller, 1777; Contracaecum sp. Railliet Henry, 1912 and Monogenea: Vancleaveus ciccinus One species showed a negative correlation between total length and average abundance for P. tigrinum, while P. fasciatum correlation was positive for three species. The comparison of abundance averages by sex for P. tigrinum showed no significant difference between groups, for P. fasciatum a significant difference was observed among the individuals parasitized by Peltidocotyle sp., Monticellia sp., Nominoscolex sp. where females showed higher average abundance in relation to males.